Enhanced climate instability in the North Atlantic and southern Europe during the Last Interglacial - P. C. Tzedakis (Nature Portfolio, 2018)
It is important to establish a baseline for natural climate variability under relatively warm conditions. Here we show that the Last Interglacial in the North Atlantic and southern Europe was characterized by enhanced climate instability relative to the pre-industrial Holocene.